A Theoretical Study of Phytochemicals as Green Corrosion Inhibitors: Sebuah Studi Teoritis Tentang Fitokimia sebagai Penghambat Korosi Hijau - Mustafa Jassim Radhi; Israa Mohsen Mizeel (Academia Open, 2024)
In this research, the effectiveness role of phytochemicals as agents for inhibiting corrosion was studied, including eugenol, cinnamaldehyde, and cinnamic acid. All quantum chemical calculations related to the phytochemical molecules studied using Biovia software and DFT technique are presented. A comparison of the adsorption properties on the iron(110) surface and corrosion inhibition of the studied phytochemicals is discussed .Furthermore, computational methods involving Monte Carlo simulations and molecular dynamics were employed to evaluate adsorption energies and stable configurations of inhibitors at the iron (110) surface. The phytochemicals under investigation have the following adsorption energies: Eugenol Eads = -98.442869 kcal/mol > Cinnamic acid Eads = -93.00807248 kcal/mol > Cinnamon Eads = -87.671968 kcal/mol. All theoretical studies confirmed that the surface adsorption effectiveness and corrosion inhibition performance of the studied phytochemicals follow the sequence; Eugenol (HH3) > cinnamic acid (HH2) > cinnamaldehyde (HH1). Highlights: hytochemicals (eugenol, cinnamaldehyde, cinnamic acid) studied for corrosion inhibition. Quantum chemical calculations and DFT technique used for adsorption properties. Adsorption energy sequence: Eugenol > Cinnamic acid > Cinnamaldehyde. Keywords: phytochemicals , DFT , corrosion inhibitors